2023
DOI: 10.3126/irjmmc.v4i2.56014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tiffin Practices on the Health of School Students in Makawanpur District, Nepal

Ram Prasad Adhikari,
Bhashkar Chandra Adhikari,
Ashmita Dhimal
et al.

Abstract: The main goals of the study are to explore the existing tiffin practices among school students, and assess the effects of tiffin practices on their health. The study was conducted in 2023, among 100 students of four schools out of 65 community schools in Hetauda sub-metropolitan in Makawanpur district. Second stage cluster sampling method was adopted to select the study area and the students were selected with simple random sampling method from different grades (1-12) of the community schools of Hetauda sub-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
1

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
2
0
1
Order By: Relevance
“…It was observed that 68% of the participants had good practice of menstrual hygiene. Consistent results were reported in the country, central (51.3%), 49 east Shewa (66.8%), 25 northwest (68%) Ethiopia, 53 and Kenya (28.8%). 30 In addition, a very low practice was reported from Uganda, which indicated that only 9.5% practice good menstrual hygiene.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…It was observed that 68% of the participants had good practice of menstrual hygiene. Consistent results were reported in the country, central (51.3%), 49 east Shewa (66.8%), 25 northwest (68%) Ethiopia, 53 and Kenya (28.8%). 30 In addition, a very low practice was reported from Uganda, which indicated that only 9.5% practice good menstrual hygiene.…”
Section: Discussionsupporting
confidence: 79%
“…This could be a risk factor for increased bacterial growth as more than three-fourths of this study participants responded they did not use sunlight for drying. An analogous result was reported from Ethiopia 22,53 and South India 5 which might enable to access MHM material. 39,63…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation